Heterocyclic imidazo-anthraquinone as an optical sensor: synthesis, characterization and evaluation of the chemosensory ability - Ferreira, Rosa Cristina Moutinho (2017)
A novel imidazo-anthraquinone derivative 3 was synthesized in moderate yield. The photophysical properties of the new compound were studied by UV-vis and fluorescence spectroscopy in ACN. The evaluation of the new compound as a colorimetric chemosensor was carried out by performing spectrophotometric titrations in ACN and ACN/H2O in the presence of relevant organic and inorganic anions and transition metal cations. Imidazo-anthraquinone 3 exhibited great selectivity for the cyanide anion over other anions in ACN/H2O (95:5) solution showing a distinct color change from yellow to pink.